Behavioral Health Promotion and Intervention in Intellectual and Developmental Disabilities - Luiselli, James K.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book discusses the latest evidence-based practices and how they can be implemented to address health problems in people with intellectual and developmental disabilities (IDD). It offers various intervention and prevention strategies for treating commonly encountered issues in patients with IDD, such as eating and sleeping disorders, repetitive self-harming behaviors, and personal hygiene problems. Primary strategies include encouraging healthful habits, reducing noncompliance and risk-taking behaviors, and direct intervention to promote optimum functioning while reducing discomfort, frustration, and adverse behaviors. In addition, contributors describe training and consultation models to enable readers to work more effectively with practitioners, clinicians, and parents as well as with the patients themselves. Topics featured in this book include: Compliance with medical routines. Increasing and maintaining exercise and other physical activities. Assistive technologies in severe and multiple disabilities. Substance use and health-related issues. Consultation with medical and healthcare providers. Parent training and support. Behavioral Health Promotion and Intervention in Intellectual and Developmental Disabilities is a valuable resource for researchers, clinicians, and graduate students in clinical psychology, behavioral therapy/rehabilitation, social work, public health, and other interrelated fields.
Health Conditions, Learning, and Behavior -- Compliance with Medical Routines -- Personal Hygiene -- Increasing and Maintaining Exercise-Physical Activity -- Assistive Technology in Severe and Multiple Disabilities -- Body-Focused Repetitive Behaviors -- Food Refusal and Selective Eating -- Sleep and Sleep-Related Problems -- Rumination Disorders -- Substance Use and Health Related Issues -- Consultation with Medical and Healthcare Providers -- Parent Training and Support.
Keywords: Psychology, Clinical; Behavioral Therapy; Clinical Psychology